Power Struggle in August Strindberg’s The Father: A Foucauldian Analysis - Safaa, Fahes (European Scientific Journal, ESJ, 2023)
The bulk of critical works on August Strindberg’s The Father use biographical material and Strindberg’s misogyny to assert the struggle between the sexes in The Captain’s tragic victimization by his domineering wife, Laura, while a few other works have presented the play as a dramaturgy of struggle for power between an aristocratic man and his bourgeoisie wife. Following Foucault’s approach on power, this paper argues that although both Laura and The Captain actively participate in exercising power using discourses and knowledge, it is ultimately Laura’s manipulation of these two strategies along with allegation of insanity that give her the upper hand and guarantee her ascension to sovereignty in the household.